Reconstructing calcification in ancient coccolithophores: Individual coccolith weight and morphology of Coccolithus pelagicus (sensu lato) - Cubillos, JC; Henderiks, J; Beaufort, L; Howard, WR; Hallegraeff, GM (Marine Micropaleontology, 2012)
We have adapted an existing method to estimate coccolith calcite weight using birefringence (Beaufort,2005) to suit the large coccoliths of Coccolithus pelagicus , which are only partially birefringent under crosspolarisedlight microscopy. Fossil and sediment trap material from the South Tasman Rise region of theSouthern Ocean was used for calibration and validation. Our approach was tested with only the coccolith centralarea (CA) considered for measurement, to avoid relying on the less robust proximal shields. Thus our resultsare relative and intend to quantify intra-specific variations in volumetric calcite weight, expressed as aWeight Index (WI). Our results were overall consistent with mass estimation based on distal shield lengths.However, the WI approach clearly has the advantage in exploring allometric scaling between coccolith sizeand weight, as well as in measuring the degree of calcification in similarly sized morphotypes. CombiningWI and morphometry data (distal shield length, DSL), we demonstrate subtle, but statistically significantchanges in shape and thus calcification degree both within and between the tested Coccolithus populations.Most strikingly, it appears that modern Coccolithus populations in the Southern Ocean are, on average,more heavily calcified than their fossil counterparts.